(untitled) (Research, Society and Development, 2022)
Human food is governed by geographic, religious, and historical facts. These values shaped food culture, leading to perceptions and adoption of their own sensory attributes, characterizing the knowledge and flavors of Mexican cuisine. Mexico is an example of a country with great cultural miscegenation, where the native indigenous culture in contact with Spanish gastronomy, mixed local and foreign foods, got to know foods and new culinary techniques, adapted, and propitiated the emergence of Mexican mestizo gastronomy. An important part of this food culture is the sweets, governed by indigenous precepts and traditions, added to European techniques and recipes. The identity of this hybridization created a unique scenario, different from the rest of the world, where sweet is suppressed by other stronger and more striking sensations, such as sour and spicy. The problem is that this topic is not widely addressed in the academic gastronomic universe, where part of the information that is already so scarce is transmitted orally or informally, bringing a risk to the effective perpetuation of Mexican gastronomic knowledge, where the registration of cultural values is a fundamental component for the consolidation of gastronomy as an intangible heritage in the historicity of humanity. This work aimed to carry out a bibliographic review on Mexican sweets, permeating their history and origin within the Mexican food culture.